Immunomolecular response of CD4+, CD8+, TNF-α and IFN-γ in Myxobolus-infected koi (Cyprinus carpio) treated with probiotics - Uun Yanuhar; Nico Rahman Caesar; Nur Sakinah Junirahma; Rachmat Noer Soelistyoadi (Aquaculture and Fisheries, 2023)
A poor environment increases fish's susceptibility to myxosporean infection that can cause the death of larval fish, especially for koi fish (Cyprinus carpio). This study aimed to determine the effect of probiotics, local anti-parasitic drugs (kutuklin), and the chemical compound diflubenzuron treatments on the koi immune response. This study used PCR with specific primer 18S SSU rDNA and DNA sequencing to detect Myxobulus phylogenetic. The treatments were divided into 5 groups: Treatment (A) (healthy koi without treatment), (B) (infected koi without treatment), (C) (infected koi with 0.55 mL/30 L probiotics), (D) (infected koi with 1 μL/g of feed kutuklin), and (E) (infected koi with 0.02 mg/5 L dimilin). Myxospore has observed with Scanning Electron Microscopy (SEM) and 4′,6-diamidino-2-phenylindole (DAPI) fluorescence staining. The histological analysis using semi-quantitative scoring methods, and flow cytometry was conducted to analyse the immune response of Cluster of differentiation 4 (CD4+), Cluster of differentiation 8 (CD8+), Tumor Necrosis Factor-alpha (TNF-α), Interferon gamma (IFN-γ) cells in the gills. Results show that the histological analysis indicated edema, hyperplasia, lamella fusion, congestion, and hypertrophy lesions in infected koi. Treatment with probiotics shows the lowest damage (30.6%). The immune responses of CD4+ and CD8+ cells to dimilin treatment were 10.54% and 16.86%, respectively. The largest TNF-α and IFN-γ response were for the kutuklin treatment (29.26%) and probiotics treatment (8.23%).